2005
DOI: 10.5194/npg-12-775-2005
|View full text |Cite
|
Sign up to set email alerts
|

A Kalman filter application to a spectral wave model

Abstract: Abstract.A sequential time dependent data assimilation scheme based on the Kalman filter is applied to a spectral wave model. Usually, the first guess covariance matrices used in optimal interpolation schemes are exponential spreading functions, which remain constant. In the present work the first guess correlation errors evolve in time according to the dynamic constraints of the wave model. A system error noise is deduced and used to balance numerical errors.The assimilation procedure is tested in a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Echevin et al (2000) found that the EnKF can capture the anisotropic covariance functions resulting from the impact of the coastlines and of the coastal dynamics, being particularly advantageous over other methods. A similar method was also used by Pinto et al (2005) to predict the wave height in a spectral wave model.…”
Section: The Ensemble Kalman Filtermentioning
confidence: 99%
“…Echevin et al (2000) found that the EnKF can capture the anisotropic covariance functions resulting from the impact of the coastlines and of the coastal dynamics, being particularly advantageous over other methods. A similar method was also used by Pinto et al (2005) to predict the wave height in a spectral wave model.…”
Section: The Ensemble Kalman Filtermentioning
confidence: 99%
“…There are however some attempts to assimilate the wave data at the buoy of Sines for limited periods of time related to the Navy exercises. 32,33 From this perspective, the present work presents a simple, but effective, SCM-DA scheme that was implemented in an operational wave prediction system with the direct objective to increase the accuracy of the wave predictions in the vicinity of the major Portuguese ports.…”
Section: Rusu and C Guedes Soares Fimarest Centre For Marine Technmentioning
confidence: 99%
“…Up to now, many KF-derived DA methods have been proposed. The KF method explicitly computes the error covariances through an additional matrix equation that propagates error information from one update time to the next, subject to possibly uncertain model dynamics [4,5]. When the LSMs are linear, the KF method not only can get the optimal estimate of the SVLs, but also can estimate the error of the optimal estimate.…”
Section: Advances In Meteorologymentioning
confidence: 99%